Analisis Arus dan Kecepatan Kendaraan pada Ruas Jalan Nasional Kota Gorontalo dengan Metode Moving Car Observer - Tria Adisty Nursahraini aini; Yuliyanti Kadir; Frice L. Desei (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The national roads in Gorontalo City serve as the main transportation routes connecting the city to other regions in Sulawesi and even across provinces. This research aims to analyze traffic flow and vehicle speed, as well as to predict traffic growth over the next ten years using the Moving Car Observer method. The study was conducted on four national road segments: Prof. Dr. H.B. Jassin Street, Nani Wartabone Street, Yos Sudarso Street, and Mayor Dullah Street. Data were collected through moving vehicle surveys and analyzed using formulas from the Bina Marga Traffic Travel Time Calculation Guide No. 001/T/BNKT/1990. The results of the study show that the highest traffic flow occurred on H.B. Jassin road in the afternoon, reaching 1,264 PCU/hour, while the lowest was recorded on Yos Sudarso road in the afternoon at 250.4 PCU/hour. The highest speed was observed on Mayor Dullah road in the afternoon at 28.09 km/h, and the lowest on H.B. Jassin road in the afternoon at 18.37 km/h. Specifically, H.B. Jassin road experienced a 25.4% increase in traffic flow with a 22.8% decrease in speed; Nani Wartabone road saw a 34.7% increase in flow and a 3.1% increase in speed; Yos Sudarso road experienced an 11.8% decrease in flow and an 8.5% decrease in speed; while Mayor Dullah road showed a 29.3% increase in flow and a 10.5% increase in speed.